2021
DOI: 10.1128/spectrum.01539-21
|View full text |Cite
|
Sign up to set email alerts
|

The Archaeal Transcription Termination Factor aCPSF1 is a Robust Phylogenetic Marker for Archaeal Taxonomy

Abstract: Archaea represent a unique type of prokaryote, which inhabit in various environments including extreme environments, and so define the boundary of biosphere, and play pivotal ecological roles, particularly in extreme environments. Since their discovery over 40 years ago, environmental archaea have been widely investigated using the 16S rRNA sequence comparison, and the recently developed phylogenomic approach because the majority of archaea are recalcitrant to laboratory cultivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…In archaea, the U-rich terminators with 5, 6, and 7 consecutive Us (U5, U6, and U7) have been reported to be widely distributed in transcript 3′-ends ( Berkemer et al, 2020 ; Dar et al, 2016a ; Maier and Marchfelder, 2019 ; Yue et al, 2020 ); meanwhile, the aCPSF1 orthologs have also been found to be strictly conserved and appear being vertically inherited ( Li et al, 2021 ; Phung et al, 2013 ; Yue et al, 2020 ). Therefore, we questioned whether the cooperative mode of aCPSF1 and the terminator U-tract is a common termination mechanism in archaea.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In archaea, the U-rich terminators with 5, 6, and 7 consecutive Us (U5, U6, and U7) have been reported to be widely distributed in transcript 3′-ends ( Berkemer et al, 2020 ; Dar et al, 2016a ; Maier and Marchfelder, 2019 ; Yue et al, 2020 ); meanwhile, the aCPSF1 orthologs have also been found to be strictly conserved and appear being vertically inherited ( Li et al, 2021 ; Phung et al, 2013 ; Yue et al, 2020 ). Therefore, we questioned whether the cooperative mode of aCPSF1 and the terminator U-tract is a common termination mechanism in archaea.…”
Section: Resultsmentioning
confidence: 99%
“…Most recently, aCPSF1, also named FttA ( F actor that t erminates t ranscription in A rchaea), has been demonstrated as a transcription termination factor of archaea because it could competitively disrupt the processive TEC at normal transcription elongation rate and implement a kinetically competitive termination dependent on both the stalk domain of RNAP and the transcription elongation factor Spt4/5 in vitro ( Sanders et al, 2020 ). aCPSF1 is affiliated within the β-CASP ribonuclease family, and is ubiquitously distributed in all archaeal phyla ( Li et al, 2021 ; Phung et al, 2013 ; Yue et al, 2020 ). Initially, aCPSF1 was assumed to function in RNA maturation and turnover of Archaea ( Clouet-d’Orval et al, 2015 ), and endoribonuclease activity was identified for three aCPSF1 orthologs in vitro ( Levy et al, 2011 ; Phung et al, 2013 ; Silva et al, 2011 ), with one also exhibiting 5′–3′ exoribonuclease activity ( Phung et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…This species is also regarded as a model archaeon in archaeal biology research, such as in transcription and posttranscription regulation ( 33 35 ), motility characteristics ( 36 , 37 ), featured CO 2 and N 2 fixation, and methanogenic metabolism ( 38 45 ). By taking advantage of its genetic system, we previously found the long-sought transcription termination factor aCPSF1 and its mediated archaeal termination mechanism, which represents a bacterium-distinct and simplified archetypal mode of eukaryotic RNA polymerase II termination machinery ( 14 , 34 ). However, although the conventional genome editing tools for M. maripaludis have contributed greatly to the knowledge of archaeal biology and potential biotechnological applications, further improvements are warranted to achieve faster, more efficient, and more versatile genome editing, which will enhance M. maripaludis as a model in archaeal biology and a chassis in archaeal biotechnology.…”
Section: Introductionmentioning
confidence: 99%